A chromosome-scale assembly of the sorghum genome using nanopore sequencing and optical mapping - Stéphane Deschamps (Nature Portfolio, 2018)
Assembly of large, repeat-rich eukaryotic genomes remains challenging. Here, the authors use BioNano Genomics DLS optical mapping and single-molecule nanopore sequencing to generate a chromosome-scale assembly of a new Sorghum bicolor accession and identify variation compared to the publicly available S. bicolor genome.